Parameters of immunological competence in subjects with high consumption of fish contaminated with persistent organochlorine compounds - Svensson, B G; Hallberg, T; Nilsson, A; Schütz, A; Hagmar, L (International archives of occupational and environmental health, 1994)
Consumption of fatty fish species, like salmon and herring, from the Baltic Sea is an important source of human exposure to persistent organochlorine compounds, e.g. polychlorinated dioxins (PCDDs), dibenzofurans (PCDFs) and biphenyls (PCBs). Many of these compounds show immunotoxic and hepatotoxic effects in animals. We have now studied immunological competence, including lymphocyte subsets, in 23 males with a high consumption of fish from the Baltic Sea and in a control group of 20 males with virtually no fish consumption. The high consumers had lower proportions and numbers of natural killer (NK) cells, identified by the CD 56 marker, in peripheral blood than the non-consumers. Weekly intake of fatty fish correlated negatively with proportions of NK cells (rs = -0.32, P = 0.04). There were also, in a subsample of 11 subjects, significant negative correlations between numbers of NK cells and blood levels of a toxic non-ortho-PCB congener (IUPAC 126; rs = -0.68, P = 0.02) and a mono-ortho congener (IUPAC 118; rs = -0.76, P = 0.01). A similar correlation, in 12 subjects, was seen for p,p'-DDT (rs = -0.76, P = 0.01). The corresponding negative correlation, in 13 subjects, with blood levels of PCDD/Fs was not significant (rs = -0.57, P = 0.07). No significant association was seen between organic mercury in erythrocytes and NK cells. Fish consumption was not associated with levels of any other lymphocyte subset. Neither were there any correlations with plasma immunoglobulins or liver enzyme activities. Our study indicates that accumulation of persistent organochlorine compounds in high consumers of fatty fish may adversely affect NK cell levels.